PENERAPAN MODEL PEMBELAJARAN STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA - Asep Sodikin (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2020)
This study aims to improve the learning outcomes of class VIII-A students of MTs Negeri 4 Garut in science subjects on various systems of plant life. This type of research is a classroom action research conducted in two cycles, each of which is carried out in 2 meetings. Each meeting consists of the planning, action, observation and reflection stages. The subjects in this study were all students of class VIII-A MTs Negeri 4 Garut in the odd semester of the 2017-2018 school year, totaling 29 students. The data obtained in this study included: learning outcomes and student learning completeness which were taken from giving test questions at the end of each meeting and student activity in the learning process. From the research data, it was obtained that the average student learning outcomes in cycle I was 81 and cycle II was 96. The average completeness of learning in cycle I was 79% and cycle II was 100%. From these data, it is clear that from cycle I to cycle II there is a significant increase. From this research, it is concluded that by using the cooperative learning model Student Teams Achievement Divisions (STAD) can improve the learning outcomes of class VIII-A students of MTs Negeri 4 Garut in science subject on various systems in plant life.